2021
DOI: 10.3171/2020.7.jns201429
|View full text |Cite
|
Sign up to set email alerts
|

The role of cell-free DNA in fibrinolysis for intraventricular hemorrhage

Abstract: OBJECTIVETissue plasminogen activator (tPA) fibrinolysis did not improve functional outcomes of patients with intraventricular hemorrhage (IVH), largely because of the unsatisfactory clot clearance. The presence of neutrophil extracellular traps (NETs) within the clot has been confirmed to impair tPA fibrinolysis, but the mechanism has been unclear. The authors hypothesized that cell-free DNA (cfDNA), the main framework of NETs, might be the important reason for the fibrinolysis resistance, and they validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Furthermore, Middleton et al reported that NETs contribute to COVID-19-associated lung injury and microthrombosis, and lung autopsy confirmed microthrombi containing NETs with neutrophil-platelet infiltration [3]. We reported that in a rat model of intracerebral hemorrhage and intraventricular hemorrhage, where large numbers of NETs are formed in and around the hematoma, the use of tPA in combination with recombinant deoxyribonuclease1 (DNase1) to break down NETs accelerates hematoma clearance and reduces hydrocephalus, whereas cell-free DNA, the main skeletal structure of NETs, caused delayed hematoma clearance and aggravated brain damage [4,5]. In neuroinflammation after subarachnoid hemorrhage (SAH), neutrophils play an important and complex role [6].…”
mentioning
confidence: 99%
“…Furthermore, Middleton et al reported that NETs contribute to COVID-19-associated lung injury and microthrombosis, and lung autopsy confirmed microthrombi containing NETs with neutrophil-platelet infiltration [3]. We reported that in a rat model of intracerebral hemorrhage and intraventricular hemorrhage, where large numbers of NETs are formed in and around the hematoma, the use of tPA in combination with recombinant deoxyribonuclease1 (DNase1) to break down NETs accelerates hematoma clearance and reduces hydrocephalus, whereas cell-free DNA, the main skeletal structure of NETs, caused delayed hematoma clearance and aggravated brain damage [4,5]. In neuroinflammation after subarachnoid hemorrhage (SAH), neutrophils play an important and complex role [6].…”
mentioning
confidence: 99%
“…Previous studies have demonstrated the occurrence of NET formation in arterial thrombi following acute cerebral ischemia. In our previous study, significant neutrophil infiltration and NET formation were observed following IVH 38 . Subsequently, in our study on SAH, we observed the colocalization of NETs with fibrinogen-positive microthrombi 29 .…”
Section: Discussionmentioning
confidence: 73%
“…injection of 300 U (2 µL) DNase I 1 h after IVH induction. Subsequent injections of DNase I (150 U/μL in 2 µL) were administered at 12-h intervals until the predetermined time points 38 . For IF staining, Western blot (WB) analysis, RT‒qPCR, and enzyme-linked immunosorbent assay (ELISA), the meninges were collected 24 h after IVH.…”
Section: Methodsmentioning
confidence: 99%
“…SYTOX Orange staining was performed as previous described ( 21 ). Sections were stained with SYTOX Orange (Molecular Probes, Inc.) at a concentration of 5 μM for 10 min.…”
Section: Methodsmentioning
confidence: 99%